Knockdown of the atypical protein kinase genes GhABC1K2-A05 and GhABC1K12-A07 make cotton more sensitive to salt and PEG stress - Caixiang Wang; Meili Li; Dingguo Zhang; Xueli Zhang; Juanjuan Liu; Junji Su (Journal of Integrative Agriculture, 2024)
Activity of bc1 complex kinase (ABC1K) is an atypical protein kinase (aPK) that plays a crucial role in plant mitochondrial and plastid stress responses, but little is known about the responses of ABC1Ks to stress in cotton (Gossypium spp.). Here, we identified 40 ABC1Ks in upland cotton (Gossypium hirsutum L.) and found that the GhABC1Ks were unevenly distributed across 17 chromosomes. The GhABC1K family members included 35 paralogous gene pairs and were expanded by segmental duplication. The GhABC1K promoter sequences contained diverse cis-acting regulatory elements relevant to hormone or stress responses. The qRT-PCR results revealed that most GhABC1Ks were upregulated by exposure to different stresses. GhABC1K2-A05 and GhABC1K12-A07 expression levels were upregulated by at least three stress treatments. These genes were further functionally characterized by virus-induced gene silencing (VIGS). Compared with the controls, the GhABC1K2-A05- and GhABC1K12-A07-silenced cotton lines exhibited higher malondialdehyde (MDA) contents, lower catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) activities and reduced chlorophyll and soluble sugar contents under NaCl and PEG stress. In addition, the expression levels of six stress marker genes (GhDREB2A, GhSOS1, GhCIPK6, GhSOS2, GhWRKY33, and GhRD29A) were significantly downregulated after stress in the GhABC1K2-A05- and GhABC1K12-A07-silenced lines. The results indicate that knockdown of GhABC1K2-A05 and GhABC1K12-A07 make cotton more sensitive to salt and PEG stress. These findings can provide valuable information for intensive studies of GhABC1Ks in the responses and resistance of cotton to abiotic stresses.